Isokinetic peak of torque and fatigue index in simulated wheelchair propulsion in elite wheelchair rugby players - Machado, F.; Correia, R. F.; Ribeiro, A. N.; Ribeiro dos Santos Neto, S.; Brandao Vieira, I.; Gorla, J. I. (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: In sports such as wheelchair rugby, the correct assessment and quantification of an athletes` peak of torque and fatigue index in sport-specific actions are essential in monitoring an athletes` training performance. The increase in the number of people practicing Paralympic sports has been growing exponentially, contributing to an increase of competition level and of athletes` performance. Objective: Thus, physical training for Paralympic sport must aim to maximize athletes` fitness potential by investigating and evaluating what variables are most important in determining ideal sporting performance. Methods: Six high-level wheelchair rugby athletes had their wheelchair propulsion peak of torque and fatigue index evaluated by isokinetic dynamometry in three different angular velocity and repetition schemes. Results: The athletes presented no significant statistical difference in peak of torque and fatigue index for both arms at different number of repetitions and angular velocity. Conclusions: This shows that independent of dexterity parameters or duration of stimuli, these high-level athletes display this motor skill in constant levels of performance. These results will allow coaches to set up normative parameters to test and evaluate their players` performances.